2012
DOI: 10.1089/lap.2011.0440
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for Postoperative Wound Pain in Gynecologic Laparoscopic Surgery: Topical Lidocaine Patches

Abstract: Topical lidocaine patches at the laparoscopic port sites reduced postoperative pain, particularly postoperative wound pain after gynecological laparoscopic procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 21 publications
1
33
1
Order By: Relevance
“…106 Evidence for the lidocaine 5% patch for acute postoperative pain is limited. [107][108][109][110] A meta-analysis of lidocaine patch shows that lidocaine patches may not be an effective adjunct for acute and postoperative pain management. 111 No significant difference of postoperative pain intensity, opioid consumption and length of hospital stay was found between the lidocaine group and the placebo group.…”
Section: Lidocaine Patchmentioning
confidence: 99%
“…106 Evidence for the lidocaine 5% patch for acute postoperative pain is limited. [107][108][109][110] A meta-analysis of lidocaine patch shows that lidocaine patches may not be an effective adjunct for acute and postoperative pain management. 111 No significant difference of postoperative pain intensity, opioid consumption and length of hospital stay was found between the lidocaine group and the placebo group.…”
Section: Lidocaine Patchmentioning
confidence: 99%
“…Data were available on 251 patients. There were four randomized controlled trials [15][16][17][18] and one prospective cohort study 19 . For the prospective cohort study, during the first 6 month period patients received the lidocaine patch, with patients from the subsequent 6 month period serving as controls.…”
Section: Resultsmentioning
confidence: 99%
“…For the prospective cohort study, during the first 6 month period patients received the lidocaine patch, with patients from the subsequent 6 month period serving as controls. The characteristics of the included studies [15][16][17][18][19] are shown in Table 1. The flow diagram of the search process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations